2011
DOI: 10.1007/s10439-011-0294-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Microvascular Blood Flow Analysis During Post-Occlusive Reactive Hyperemia Test in Patients with Schizophrenia

Abstract: Patients suffering from schizophrenia have an increased mortality risk due to cardiovascular events. Recently the analysis of peripheral circulation has revealed interesting results in the study of vascular pathological conditions assuming that the state of microcirculation of the skin is at least partly representative for the constitution of other vascular beds including those of the cardiac muscle and arteries. The objective of this study was to investigate the microcirculation in patients with acute schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Our study provides a comprehensive assessment of macro- and microvascular endothelial functions via VTI, PAT, and FMD in subjects with schizophrenia and matched healthy controls to the age of 45. Our findings are consistent with other studies that have found a attenuation of microvascular endothelial function; however, these studies used Laser-Doppler flowmetry, which measures blood flow in the superficial dermal plexus 50 , 51 or applied retinal vasculature assessment. 52 Although both groups were matched for age, sex, and smoking status, we still observed differences in other demographic and clinical parameters.…”
Section: Discussionsupporting
confidence: 92%
“…Our study provides a comprehensive assessment of macro- and microvascular endothelial functions via VTI, PAT, and FMD in subjects with schizophrenia and matched healthy controls to the age of 45. Our findings are consistent with other studies that have found a attenuation of microvascular endothelial function; however, these studies used Laser-Doppler flowmetry, which measures blood flow in the superficial dermal plexus 50 , 51 or applied retinal vasculature assessment. 52 Although both groups were matched for age, sex, and smoking status, we still observed differences in other demographic and clinical parameters.…”
Section: Discussionsupporting
confidence: 92%
“…11 Patients with schizophrenia have impaired endothelial and microvascular peripheral blood flow response, while patients with BD have elevated levels of biomarkers associated with endothelial function. [12][13][14][15][16][17] There is also strong evidence for increased oxidative stress in SMI. A meta-analysis of 44 studies found increased markers of oxidative stress in patients with BD, seen in unmedicated patients, but not in those receiving effective antipsychotic therapy.…”
mentioning
confidence: 99%
“…Bär et al [3,4] found a significant reduction of baroreflex sensitivity and heart rate variability as well as an increase of QT variability in schizophrenic patients indicating an autonomic imbalance. Recently the analysis of peripheral microcirculation by means of Laser Doppler Flowmetry (LDF) has revealed a significantly altered microcirculation in patients with acute schizophrenia compared to healthy subjects [5]. The LDF is a non-invasive technology that facilitates the study of microcirculation via spectral analysis of the LDF signal.…”
Section: Introductionmentioning
confidence: 99%